INTERNALISASI SAMMA AJIVA BAGI UMAT BUDDHA SEBAGAI DASAR PERTIMBANGAN MENCARI PENGHIDUPAN - Danang Try Purnomo; Ade Sukma (Jurnal Pendidikan, Sains Sosial, dan Agama, 2020)
This study discusses the profession reviewed from the concept of Buddhism. The purpose of this research is to describe the profession (livelihood) in accordance with Buddhism. This type of research is descriptive qualitative. The data was obtained from in-depth interviews and literature studies. Based on field surveys, Buddhists have a common livelihood that conforms to the samma ajiva concept of 'true livelihood' in Buddhism. Buddhist society also plays an important role for the continuity of the livelihood sector in villages and cities because basically Indonesian society consists of various religions that become their own beliefs. Therefore, there is no difference in doing a work related to belief, which is emphasized more is the worth of a livelihood in the View of Buddhism. Keywords: profession, livelihood, Buddhist society